Dose reporting and dose-stratified effects of early mobilization in mechanically ventilated adult ICU patients: a systematic review and meta-analysis - Hong Zhou; Shengting Li; Tingting Tu; Xiulan Yang; Mingtao Quan; Zhihui Shang; Xia Zhang (Frontiers in Medicine, 2026)
Background This systematic review and meta-analysis aimed to evaluate how early mobilization dose is reported and to explore dose-stratified effects of early mobilization on functional recovery, clinical outcomes, diaphragmatic function, and safety in mechanically ventilated adult ICU patients. Methods Eight electronic databases were searched from inception to May 2026. Randomized controlled trials involving mechanically ventilated adult intensive care unit patients were included. Two reviewers independently screened studies, extracted data, and assessed risk of bias using the Cochrane Risk of Bias tool. Early mobilization interventions were classified as low-, moderate-, or high-dose according to frequency, duration, and intensity. Results Thirty-one randomized controlled trials involving 3,498 participants were included. Overall, early mobilization improved functional and selected clinical outcomes, without significantly affecting mortality [RR = 1.13, 95% CI (0.89, 1.42), P = 0.258]. In dose-stratified analyses, the moderate-dose subgroup showed the most favorable effects on ICU-acquired weakness [RR = 0.19, 95% CI (0.09, 0.41)] and ICU length of stay [MD = −4.14, 95% CI (−5.00, −3.27), P < 0.001]. For adverse events, significant reductions were observed in the moderate-dose [RR = 0.41, 95% CI (0.25, 0.67), P < 0.001] and low-dose subgroups [RR = 0.25, 95% CI (0.11, 0.57), P = 0.001], but not in the high-dose subgroup [RR = 0.85, 95% CI (0.21, 3.54), P = 0.822]. Conclusions Incomplete and inconsistent reporting of mobilization dose may partly explain the variability in meta-analytic findings across early mobilization trials. Moderate- to high-dose mobilization appears to be associated with more favorable outcomes when tailored to clinical resources and patient tolerance. Given the substantial heterogeneity across studies, future trials should standardize the definition and reporting of mobilization dose to support individualized and resource-optimized mobilization strategies. Systematic Review Registration PROSPERO, CRD420261416276.